Neuroarquitetura e Fenomenologia: O visível e o invisível na experiência sensorial do ambiente construído (Phenomenology, Humanities and Sciences, 2025)
This article investigates the intersection between neuroarchitecture and phenomenology, focusing on the work of Maurice Merleau-Ponty, particularly in Le Visible et l'Invisible. Neuroarchitecture, which merges neuroscience and architecture, examines how the built environment affects the brain and human behavior. Merleau-Ponty's phenomenology, emphasis on intercorporeality and embodied perception, provides a significant theoretical foundation for understanding the interactions between body, space, and sensory experience. The article discusses how the body shapes spatial perception and how the aesthetic experience in the built environment transcends mere visuality, involving a profound sensory and emotional interaction with the environment. The implications of these ideas for the practice of neuroarchitecture are also explored, proposing an approach that considers space as an extension of the human being, capable of influencing and being influenced by perceptual and existential experiences. Thus, a more sensitive architecture is suggested, one that not only meets functional needs but also enhances the quality of life, promotes human connection, and enriches the experience of being in the world.